ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI PADI SAWAH DI DESA BONEMARAWA KECAMATAN RIOPAKAVA KABUPATEN DONGGALA - Yasa, I Nyoman Artika; Hadayani, Hadayani (AGROTEKBIS, 2017)
This research aimed to identify factors affecting the production and the income of wetland rice farming system in Bonemarawa village Riopakava subdistrict of Donggala regency. The determination of respondents was carried out through a Simple Random Sampling Method. The number of samples was 34 people taken from population of 180 people. The analytical tool used was the functional production analysis of Cobb-Douglass and income analysis. The results of analysis showed that the independent variables used in the production inputs i.e.land area, seeds, fertilizers, and labor simultaneously affected the rice production in Bonemarawa village with the    F-count > F-table (119.554 > 4.02) at the 99% confidence level. The income analysis showed     that the average income of the respondent farmers in Bonemarawa was IDR 2,915,947.85/0,68ha/planting season (PS) or IDR 4,288,158.60/ha/PS. Keywords : Income, Production,and Wetland rice.